Standing Pouch Packaging Development for Usus Hawa Chips: Enhancing Product Value - Adi Setiawan, Muhammad Ujang (Research Horizon, 2025)
This study aims to examine the impact of the development of standing pouch packaging on increasing the economic and aesthetic value of products at the UMKM Kripik Usus Hawa Snack. This UMKM is a producer of snacks made from chicken intestines that has been operating since 2020. The research method uses a qualitative approach through in-depth interviews with owners and consumers, as well as a quantitative approach through distributing questionnaires to 41 respondents from middle to upper class consumers. The results of the study showed that the old packaging used by MSMEs seemed less attractive and functional. Through an analysis of five important aspects of packaging—shape, material, color, font, and brand—it was found that the majority of respondents chose the standing pouch form (48.8%), aluminum foil material (68.3%), bright colors (75.6%), and wanted complete information on the packaging (65.9%) and a clear brand (80.5%). The implementation of the new packaging for three months showed a positive economic impact, namely an increase in selling price of 15–20%, an increase in net profit of around 10%, and increased purchasing interest, repeat orders, and demand from resellers. These findings strengthen the theory that packaging is not just a product protector, but a strategic instrument in marketing that influences quality perception and purchasing decisions. This study recommends standing pouches as an innovative packaging solution for MSMEs who want to strengthen branding, increase competitiveness, and target the premium market segment.